Potential of Nanoparticles for Postharvest of Fruits and Vegetables - Azri Shahir, Rosman; Norhashila, Hashim; Bernard, Maringgal; Intan Syafinaz, Mohamed Amin Tawakkal; Khalina, Abdan; Akhmad, Sabarudin (CRC Press. Taylor & Francis Group, 2024)
Nowadays, the demand for fresh fruits and vegetables is increasing due to rising health awareness in society. Nevertheless, fruits and vegetables are subject to senescence upon harvesting, making them unacceptable for consumption. The use of nanoparticles in postharvest storage applications has revolutionised research and piqued the interest of many people due to their well-known benefits in extending the freshness of food products. People have recognised the benefits of nanoparticles, particularly their antimicrobial and antioxidant properties, which could be used in the storage of fruits and vegetables. Yet, due to its nanoscale characteristics, controlling its specific properties is difficult, and information about its effects on human health is still scarce. More thorough research and legalisation are needed to make nanoparticle applications more acceptable to society and attract industrial marketers and investors.